Dental topographic analysis of paromomyid (Plesiadapiformes, Primates) cheek teeth: more than 15 million years of changing surfaces and shifting ecologies*. (17th February 2018) - López-Torres, Sergi; Selig, Keegan R.; Prufrock, Kristen A.; Lin, Derrick; Silcox, Mary T.
Abstract: Plesiadapiforms, appearing near the Cretaceous-Paleogene boundary, represent the first primate radiation and show a diverse array of tooth morphologies. Dental topographic metrics provide quantitative data on occlusal surface shape. We used three metrics, Dirichlet Normal Energy, Relief Index, and 3D Orientation Patch Count Rotated, to assess changes in the morphology of lower fourth premolars and lower second molars in a taxonomically broad sample of one family of plesiadapiforms, Paromomyidae, stretching more than 15 million years. Our results indicate that paromomyids occupied a more diverse range of dietary categories than suspected. Whereas all paromomyids were likely omnivores, some species show higher levels of insectivory, while other taxa are inferred to have been mixed-feeding omnivores with high levels of fruit intake. The results also show that the more primitive members of the different paromomyid lineages were more insectivorous than the derived and more recent members of those lineages. Relief Index values also show taxonomic signals that are consistent with ancestor-descendant relationships hypothesised for species of Phenacolemur . These results suggest that dental topographic metrics are informative to the study of paromomyids for both dietary categorisation and for the distinction of species at a fine taxonomic level.